PD-1/LAG-3 bispecific antibody potentiates T cell activation and increases antitumor efficacy - Shi, Ning; Zhou, Yangyihua; Liu, Yujun; Zhang, Ran; Jiang, Xingjun; Ren, Caiping; Gao, Xiang; Luo, Longlong (Frontiers in Immunology, 2022)
Several clinical studies demonstrate that there exist other immune checkpoints overexpressed in some PD-1 inhibitor-resistant tumor patients. Among them, Lymphocyte-activation gene 3 (LAG-3) is one of the important immune checkpoint molecules and has been clinically demonstrated to have synergistic anti-tumor effects in combination with PD-1 antibody. In this study, we designed a novel 'knob-in-hole' PD-1/LAG-3 bispecific antibody (BsAb) YG-003D3. In conclusion, the BsAb maintained the similar affinity and thermal stability to the parental antibody, and the BsAb structure can be independent of each other in the process of double-target recognition, and the recognition activity will not be affected. Moreover, the BsAb can not only target PD-1 and LAG-3 on single cell simulatiously, but also bridge the two kinds of cells expressing PD-1 and LAG-3, so as to release the 'brake system of immune checkpoints' and activate immune cells to exert anti-tumor effects more effectively. Especially in the PBMCs activation assay, YG-003D3 induced stronger IFN-γ, IL-6, and TNF-α secretion compared to anti-PD-1 or anti-LAG-3 single drug group or even combined drug group. In the tumor killing experiment of PBMC in vitro, YG-003D3 has a better ability to activate PBMC to kill tumor cells than anti-PD-1 or anti-LAG-3 single drug group or even combined drug group, and the killing rate is as high as 20%. In a humanized PD-1/LAG-3 transgenic mouse subcutaneous tumor-bearing model, YG-003D3 showed good anti-tumor activity, even better than that of the combination group at the same molar concentration. Further studies have shown that YG-003D3 could significantly alter the proportion of immune cells in the tumor microenvironment. In particular, the proportion of CD45+, CD3+ T, CD8+ T cells in tumor tissue and the proportion of CD3+ T, CD8+ T, CD4+ T cells in peripheral blood were significantly increased. These results suggest that YG-003D3 exerts a potent antitumor effect by activating the body 's immune system. In summary, the BsAb YG-003D3 has good anti-tumor activity, which is expected to become a novel drug candidate for cancer immunotherapy.